An analysis of the legislative framework for mobile digital signature in Malaysia / Erickka Farrise Amir ... [et al.] - Amir, Erickka Farrise; Yatimi, Nur Amni Lukman; Jamaludin, Nabila; Radzenan, Anis Radzleen (2013)
This research provides an analysis on the Legislative Framework for mobile digital signature in Malaysia. This analysis focuses on the issue whether the legislative framework for digital signature is adequate in governing mobile digital signature in Malaysia. This research is significant in view of the fact that electronic commerce transactions are on the verge of advancements in Malaysia nowadays. The law referred for this study are namely, the Digital Signature Act 1997, the Digital Signature Regulation 1998 and the Electronic Commerce Act 2006. Essentially, in comparative analysis, the laws in other countries are also referred to such as the Korean Digital Signature Act 2001 and Taiwan Electronic Signature Act. A series of literature are reviewed in this research as we analysed the comparisons between the Malaysian laws and the laws in other jurisdictions. As this topic of research is rather complex as it relates to the understanding of mobile digital signature technology, the comparative analysis would be a great help. This research proposes that the current legislative framework is inadequate in governing the issue of mobile digital signature in Malaysia. There are several recommendations provided by this research ranging from the amendment to the Digital Signature Act 1997, the improvement on the procedural aspect of the law, the enhancement on the role of judiciary and legal practitioners to the suggestion of alternative dispute resolutions. It is hoped that the findings of this research would provide a better understanding on the laws governing mobile digital signature. It is also our hope that this research would assist the policy makers in a review of the current legislative framework for mobile digital signature in Malaysia.